LAW, LEGISLATION, COOPERATION: TOWARDS A GENERAL THEORY OF COOPERATION - Warren, Jerome Nikolai (International Journal of Cooperative Law, 2023)
This contribution attempts to respond to Antonio Fici’s call for increased dialogue between law and economics on the topic of cooperatives. Concretely, it seeks to contribute two things: firstly, to ask what ageneral theoryof cooperation might look like and secondly,to outline a framework for cooperative economics. It does this by attempting to embed democracyin an economic viewpoint, via the notion of arelationalorcooperative rent and discovers that the presently dominant neoclassical model is not in a position to facilitate such a translation. It will be argued that the theory of legal imputationcan serve as a benchmark for rendering organizational decisions respective of stakeholder status. Lastly, drawing especially on work by the German legal historian Otto von Gierke, it outlines the role of a synthetic “social law” that seeks to embed individuals within a collective, connecting these ideas with contemporary discourse on complexity and cybernetics.